Uses of natural fruit (Diospyros embrypteris Pers) as a rot-proofing agent - Jafrin, Shamina; Dilruba, FA; Uddin, Md Kamal; Gomes, Isidore; Islam, Md Emdadul (Daffodil International University Journal of Science and Technology, 2010)
Two different types of hessian fabrics (sized and desized) were treated with unripe natural fruit juice ( Botanical Name: Diospyros embrypteris Pers) and copper sulphate solution. The physico-chemical properties of the treated fabrics were determined and made nursery pots for seedling to improve the longevity of rot-proof nursery pot. It was observed that 5% copper sulphate solution treated nursery pots posseses longevity 5.5 months but the extract of natural fruit juice mixed with 5% copper sulphate solution treated sample increases the longevity of nursery pot about eleven months. At the same time 8% copper sulphate solution treated nursery pots longevity more than nine months but natural fruit juice mixed with 8% copper sulphate solution treated nursery pot is required to achieve longevity about fourteen months. Uses of natural fruit gaab have no critical steps to environment, free from health hazard and durable. That's why it has some potentiality to use for making nursery pots with less chemical materials. Keywords: Rot-proof, Gaab, Copper sulphate, Longevity, Nursery Pot, Hessian, Sized, Desized DOI: 10.3329/diujst.v4i1.4349 Daffodil International University Journal of Science and Technology Vol.4(1) 2009 pp.14-17